A theoretical approach to the pale tussock moth outbreak in Turkey - Kahraman İpekdal (Turkish Journal of Forestry, 2022)
The pale tussock moth, Calliteara pudibunda, makes periodic outbreaks in Europe. The species made an unusual outbreak between 2018 and 2019 in Bursa, Turkey. The aim of this study is to investigate occurrence of any previous outbreak of the species in Turkey, and possible relationship among the forest management activities, temperature trends, and the recent outbreak. To investigate previous outbreaks, scientific reports, and theses both in English and Turkish, along with nature photography repositories and forums from Turkey were searched. Additionally, a questionnaire was conducted with retired Turkish foresters. Annual forest management reports related to the outbreak stand were reviewed to evaluate possible impact of the forest management activities conducted in the stand prior to the outbreak. Finally, change of size in a hypothetical C. pudibunda population was simulated by using different pupal mortality rate – temperature scenarios to predict the conditions under which an outbreak can occur. As a result, no evidence of a C. pudibunda outbreak prior to 2018 was found in Turkey. Forestry management reports revealed that two consecutive clear-cutting activities were conducted in 2012 and 2013 to open a power line in the outbreak stand. The temperature regime between 2008 and 2018 caused a dramatic increase in the simulated C. pudibunda populations.